ادارة السيولة بين تحديات الوفاء بالالتزامات وتحقيق الربحية تحليل قياسي لمصرف الجمهورية في ليبيا (2010-2022) (Comprehensive Journal of Science, 2025)
The study aimed to analyze and evaluate the challenges faced by Jumhouria Bank of Libya in achieving an effective balance between liquidity management and profitability during the period from 2010 to 2022. The study adopted a descriptive analytical approach and utilized audited annual financial data and advanced statistical methods to measure the impact of liquidity management on financial performance, particularly profitability.The results demonstrated a statistically significant impact of liquidity management on bank profitability, thus rejecting the main hypothesis of no such impact. The study demonstrated that efficient liquidity management positively impacts vital indicators such as investment volume, asset value, and the ability to attract deposits, which enhances equity growth opportunities and improves profitability.However, the study indicated that the decline in actual profits was primarily due to external challenges such as the country's economic recession, as well as conservative credit policies that negatively impacted the efficient use of available funds.